Open-book management : getting started - Ivancic, Cathy (Crisp Pub. Menlo ParkUS, 1997)
Explains the open-book management process by showing company leaders how to introduce employees to the company's financial information. Provides the principles and techniques needed by company leaders to teach their employees how to use the financial information to improve the company. Discusses the benefits of the open-book process.